Anthracene derivative based multifunctional liquid crystal materials for optoelectronic devices. (4th March 2020) - Wang, Yunrui; Fang, Daqi; Fu, Tianchen; Ali, Muhammad Umair; Shi, Yuhao; He, Yaowu; Hu, Zhao; Yan, Chaoyi; Mei, Zongwei; Meng, Hong
Abstract : A liquid crystal molecule with versatile properties, like the indicators of a clock, shows various applications. Abstract : Device integration is among the current research trends in the area of organic electronics and the development of multifunctional materials is crucial to accelerate the progress of integrated devices, such as organic light-emitting transistors (OLET), organic field-effect optical waveguides (OFEW) and organic electrofluorochromic (OEFC) devices. Herein, two multifunctional materials with different side chains, 2-(4-octyloxyphenyl)anthracene (AntPh-OC8 ) and 2-(4-octylphenyl)anthracene (AntPh-C8 ), based on the concept of combining liquid crystal (LC) materials featuring facile processability, highly ordered alignment and effective charge transport and an anthracene conjugated core with strong fluorescence, are designed and successfully synthesized. The photoluminescence quantum yield (PLQY) of AntPh-OC8 and AntPh-C8 is determined to be 40.9% and 37.6%, respectively, which approaches nearly 2-fold that of 2-phenylanthracene (AntPh ). Organic light-emitting diodes (OLED) based on AntPh-OC8 confirmed its solid-state blue emission with a current efficiency (CE) of 1.82 cd A −1, whereas the corresponding organic field-effect transistors (OFET) demonstrated the highest hole mobility of up to 2.59 cm 2 V −1 s −1 . Organic phototransistors (OPT) comprising AntPh-OC8 and AntPh-C8 revealed efficient photoresponsive characteristics of these newly developed materials. These demonstrations indicate the widespread potential of our newly developed materials for applications in multifunctional integrated devices. Moreover, these results indicate the encouraging role of side-chain engineering in the improvement of charge transport and fluorescence characteristics of anthracene derivatives.